PENEGAKAN HUKUM TERHADAP MASYARAKAT YANG MELAKUKAN TINDAK PIDANA MELAWAN APARAT YANG SEDANG BERTUGAS OLEH KEPOLISIAN RESOR SIMALUNGUN - Prima Rianto Hutagaol; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Law enforcement officials, especially the police often get resistance or violence while performing their duties. Especially common violence or persecution community.Based on this understanding, the authors formulate three formulation of the problem, namely: First, What are the factors that cause people commit criminal acts against the officers who were on duty by the Police Simalungun. Secondly, What are the problems faced by the law enforcement agencies to enforce the law against people who commit criminal acts against the officers who were on duty by the Police Simalungun. Third, How the efforts of law enforcement to address the problems in law enforcement against people who commit criminal acts against the officers who were on duty by the Police Simalungun. This type of research can be classified in this type of sociological juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the problems to be studied.This research was conducted at the Police Simalungun, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data terier, technical data collection in this study with interviews and literature study then analyzed qualitatively and process data and generate descriptive data and then inferdeductively.From the research there are three main issues which can be summarized as follows: First, the factors that cause people commit criminal acts against the officers who were on duty by the Police Simalungun. Second, the issues facing law enforcement in enforcing the law against people who commit criminal acts against the officers who were on duty by the Police Simelungun is still lacking law enforcement professionals, which is where the low level of public awareness, and not maximal performance of the Police. Third, the efforts of the law enforcement agencies to tackle the problem of enforcement against people who commit criminal acts against the officers who were on duty by the Police Simalungun is with preventive action, action peventif that prevention efforts are carried out prior to the criminal act in terms of crime prevention Police Criminal Investigation Unit conducted socialization. Keywords: Law Enforcement Criminal Investigation Unit-Crime-Persecution